Evaluating Chinese K-12 CFL/CSL Teachers’ Readiness Toward Interactive Reading Platforms - Qian, Junying; Phongsatha, Satha (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2023)
Purpose: This paper aims to investigate in-service Chinese teachers’ perception of TPACK and readiness for integrating Interactive Reading Platforms when teaching Chinese as a foreign language (CFL) or as a second language (CSL) at K-12 and to determine the effect of TPACK on teachers’ readiness for technology integration. Research design, data and methodology: The research is quantitative in nature, using questionnaires and survey to collect data from samples. 226 teachers responded to the online questionnaires which was based on TPACK model and contained 43 items in total after adjustment for item validation and reliability. The variables were content knowledge (CK), pedagogical knowledge (PK), pedagogical content knowledge (PCK), technological knowledge (TK), technological content knowledge (TCK), technological pedagogical knowledge (TPK) and teacher readiness (TR). Results: Descriptive statistics showed overall high competency and readiness for technology integration, but participants were least confident about TK. Multiple linear regression supported the hypothesis that TPACK could affect TR statistically significantly. TPK had the greatest impact on TR; PK second; TCK third, CK had negative effect on TR. The remaining TK and PCK showed no influence. Conclusions: More study is suggested to investigate the effect of TK and CK on TR. Recommendations and suggestions for future research have been provided.